With digital tools, farmers can lead the way to a sustainable future - International Fund for Agricultural Development (International Fund for Agricultural Development, 2025)
The article from the International Fund for Agricultural Development (IFAD) highlights how co-designed digital tools are empowering small-scale farmers in countries like Viet Nam and Brazil to drive a transition toward sustainable food systems. In the Mekong Delta, tools like WaterIntel and FarMoRe help rice farmers adopt agroecological practices to reduce inputs and emissions, while in Brazil, the Solis app enables cattle farmers to access and share knowledge on regenerative ranching. This farmer-centric approach ensures technology is practical and effective, paving the way for improved livelihoods and climate resilience.